Interventions and assessment tools addressing key concepts people need to know to appraise claims about treatment effects: a systematic mapping review - Austvoll-Dahlgren, Astrid; Nsangi, Allen; Semakula, Daniel (Systematic reviews, 2016)
People’s ability to appraise claims about treatment effects is crucial for informed decision-making. Our objective was to systematically map this area of research in order to (a) provide an overview of interventions targeting key concepts that people need to understand to assess treatment claims and (b) to identify assessment tools used to evaluate people’s understanding of these concepts. The findings of this review provide a starting point for decisions about which key concepts to address when developing new interventions, and which assessment tools should be considered.